Sustaining mental health among educators by understanding factors of students’ failure - Ibrahim, Noorazilah; Muhd Irpan, Hamidah; Muhammat Pazil, Nur Syuhada (2023)
Understanding the factors that contribute to students' failure is crucial to sustaining the mental health of educators. When educators can identify these factors, they can create a more supportive learning environment and reduce stress and frustration for them and their students. This study investigates the failure factors among students in Introduction to Statistics subject. 200 students were involved in this study and the collected data was analyzed using SPSS. Multiple linear regression is used to analyze the failure factors such as test score, absentee, gender, and repetition. Based on the findings, early warning signs can be determined by educators for struggling students, based on their attendance and test score. Gender and repetition are not important in predicting academic performance. Screening test on mathematics literacy and topic by topic understanding should be done prior to official test, so that weak students can be determined and supported. Better relationships can be developed by having effective communication on students’ needs and expectations. By understanding the factors contributing to students' failure and proactively addressing them, educators can create a more inclusive and supportive learning environment. This, in turn, can contribute to better mental health outcomes for both educators and students. To be completed